The Life of Children with Down Syndrome and Their Family: A Narrative Inquiry - Mishra, Somnath (NPRC Journal of Multidisciplinary Research, 2025)
Background: While clinical research on Down syndrome (DS) is well-established, a significant gap exists in understanding the subjective, lived realities and relational dynamics of families raising a child with DS. Prevailing research, often quantitative and deficit-focused, fails to capture the holistic processes of meaning-making, identity construction, and adaptation that occur within the family unit over time.Objectives: This study aimed to explore the nuanced life experiences of children with DS and their families through a narrative lens. It sought to understand how families interpret their journey, construct a shared identity, and develop resilience in response to a DS diagnosis, moving beyond clinical descriptions to document their unique stories.Methods: Employing a qualitative, longitudinal Narrative Inquiry methodology, in-depth semi-structured interviews and field texts were collected from three family units in Kathmandu over nine months. The approach focused on co-constructing and analyzing the families' chronological narratives, emphasizing temporality, sociality, and place.Findings: Analysis revealed three central narrative themes: 1) the negotiation between institutional expectations and lived reality, 2) the development of interdependent resilience among family members, and 3) the active re-scripting of "family success" toward unique developmental individuality. Families consistently constructed a positive, adaptive identity where the child with DS was viewed as a catalyst for deeper relational bonds, joy, and purpose.Conclusion: The study concludes that a narrative inquiry focus illuminates the strength and complexity of these families, challenging deficit-based models. It advocates for a fundamental shift toward family-centered support systems that validate and are informed by these unique stories of adaptation and resilience.Novelty: This research contributes a longitudinal, narrative perspective from a South Asian context (Nepal), centering the voices of families to humanize disability discourse and provide a foundation for culturally sensitive, narrative-informed practice and policy.